The position of the euploid blastocyst in the uterine cavity influences implantation. Issue 5 (November 2021) - Bayram, Aşina; De Munck, Neelke; Elkhatib, Ibrahim; Arnanz, Ana; El-Damen, Ahmed; Abdala, Andrea; Coughlan, Carol; Garrido, Nicolas; Vidales, Laura Melado; Lawrenz, Barbara; Fatemi, Human M.
Abstract: Research question: Does the position of the euploid blastocyst in the uterine cavity upon transfer, measured as distance in millimetres (mm) from the fundus (DFF) to the air bubble, influence implantation potential? Design: A total of 507 single/double euploid frozen embryo transfer (FET) cycles at blastocyst stage were included retrospectively between March 2017 and November 2018 at a single centre. The patients were on average 33.3 years old. The FET were performed in natural cycles ( n  = 151) or hormone replacement therapy cycles ( n  = 356). Results: Of the 507 transfers, 370 (73.0%) resulted in a pregnancy, defined as human chorionic gonadotrophin concentration over 15 mIU/ml, and 341 (67.3%) in a clinical pregnancy, with an implantation rate of 62.0% and ongoing pregnancy rate of 59.6% (302/507). When comparing the number of embryos transferred, the pregnancy rate, clinical pregnancy rate and ongoing pregnancy rate were significantly higher after double-embryo transfer (DET) ( P  = 0.002: P < 0.001 and P  = 0.002). The quality of the blastocyst in the single-embryo transfer group had a positive effect on the pregnancy rate (A versus B, P  = 0.016; A versus C, P  = 0.003) and clinical pregnancy rate (A versus C, P  = 0.013). After performing a multivariate logistic regression analysis to consider the effect of all explanatory variables, a negative effect between DFF and pregnancy ( P  = 0.001), clinical pregnancy ( P  = 0.001) and ongoing pregnancy ( P  = 0.030) was found. When all variables remained constant, an increase of 1 mm of DFF changed the odds of pregnancy by 0.882, of clinical pregnancy by 0.891 and of ongoing pregnancy by 0.925. No significant effect of DFF was found on the miscarriage outcome ( P  = 0.089). Conclusions: The depth of blastocyst replacement inside the uterine cavity may influence the pregnancy, clinical pregnancy and ongoing pregnancy rates and should be considered as an important factor to improve the success of IVF cycles.